2016
DOI: 10.1080/00325481.2016.1159118
|View full text |Cite
|
Sign up to set email alerts
|

Retina nerve fiber layer and choroidal thickness changes in obstructive sleep apnea syndrome

Abstract: The choroidal thickening in patients with OSAS may be associated with the pathophysiology of the neurodegeneration process of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…[ 3 ] Acer et al demonstrated that migraine patients without aura had decreased peripapillary RNFL thickness in temporal and nasal-superior sectors compared with control patients. [ 4 ] Ferrandez et al [ 5 ] found a decrease in RNFL thickness in patients with severe obstructive sleep apnoea which could be confirmed by Ozge et al [ 6 ] Also, Alzheimer disease was found to lead to significant RNFL thinning. [ 7 ]…”
Section: Introductionmentioning
confidence: 83%
“…[ 3 ] Acer et al demonstrated that migraine patients without aura had decreased peripapillary RNFL thickness in temporal and nasal-superior sectors compared with control patients. [ 4 ] Ferrandez et al [ 5 ] found a decrease in RNFL thickness in patients with severe obstructive sleep apnoea which could be confirmed by Ozge et al [ 6 ] Also, Alzheimer disease was found to lead to significant RNFL thinning. [ 7 ]…”
Section: Introductionmentioning
confidence: 83%
“…This suggests decreased ocular blood flow and possibly decreased CT in those patients. This suggestion evaluated with the increased CT found in the study by Ozge et al 1 is in favour of the autonomic dysfunction in patients with OSAS. We would also want to learn the thoughts of the authors about this assumption.…”
mentioning
confidence: 77%
“…We have read with interest the article entitled ‘Retina nerve fiber layer and choroidal thickness changes in obstructive sleep apnea syndrome’ by Ozge et al 1. We express our gratitude to the authors for demonstrating significant differences at some measurement points in macular and peripapillary retinal nerve fibre layer (RNFL) and choroidal thickness (CT) in patients with obstructive sleep apnoea syndrome (OSAS).…”
mentioning
confidence: 99%
“…This predominantly temporal reduction of the RNFL thickness seems to be consistent in the neuro-ophthalmologic literature, highlighting its usefulness as a biomarker of neurodegeneration. On the other hand, glaucoma leads to a greater decrease in the inferior RNFL quadrant thickness [ 17 ], and patients with obstructive sleep apnea syndrome present with RNFL thinning in the nasal quadrant and choroidal thickening (this change may be caused by the pathophysiology of the neurodegeneration process in obstructive sleep apnea syndrome) [ 18 ]. Therefore, each pathology may lead to a different fingerprint of damage in the optic nerve [ 19 ].…”
Section: Discussionmentioning
confidence: 99%